Exercise in prevention of cardiovascular diseases, as seen in population aged 40+ - Olišarová, Věra; Chloubová, Iva; Prokešová, Radka; Šedová, Lenka; Tóthová, Valérie (Ostravská univerzita v Ostravě, Lékařská fakulta, 2019)
Aim: The aim of the article is to highlight the level of education regarding exercise in the population aged 40+, and the amount of money spent on exercise by this population. Design: A quantitative descriptive study. Methods: The level of education regarding exercise was ascertained with the help of data obtained by a non-standardized questionnaire. The research set consisted of 1992 respondents aged 40 years and over in the Czech Republic. Results: Data analysis indicated that 52.9% patients had received educated regarding their physical activity at some point. Most respondents aged 40–49 years had not received any educational input. In addition, 34.5% respondents did not agree that regular exercise could have an influence on the developing of cardiovascular diseases. The sum most frequently spent on sports activities monthly was up to 500 CZK (78.3%). The respondentsʼ answers also indicate that 66.8% walk for at least 30 minutes, five or more days a week. Conclusion: Our findings indicate a need to improve levels of education regarding exercise and the prevention of cardiovascular diseases.
Pohybová aktivita v prevenci kardiovaskulárních onemocnění očima populace 40+
Keywords: cardiovascular disease; economic factor; education; exercise; nurse; prevention; kardiovaskulární nemoci; ekonomický faktor; edukace; pohybová aktivita; sestra; prevence